Red Cell Distribution Width Is Associated with Presence, Stage, and Grade in Patients with Renal Cell Carcinoma - Wang, Fang-Ming; Xu, Gongjun; Zhang, Yan; Ma, Lu-Lin (Disease Markers, 2014)
It has been reported that red blood cell width (RDW) is a marker associated with the presence and adverse outcomes of various diseases. However, no data are available on the correlation of RDW with presence, stage, and grade in patients with renal cell carcinoma (RCC) yet. By retrospectively analyzing clinical and laboratory data at baseline of histologically confirmed RCC cases and controls, the present study demonstrated that the RDW values were significantly higher in patients with RCC than those in controls, and the baseline RDW value was independently associated with the presence of RCC. Besides, the data revealed a positive association between RCC stage and grade and the level of RDW. These findings may have important clinical implications due to future application using a RDW value in predicting RCC.